DNA typing for personal identification of urine after long‐term preservation for testing in doping control. Issue 8 (18th November 2016) - Aoki, Kimiko; Tanaka, Hiroyuki; Ueki, Makoto
Abstract : When the tampering of a urine sample is suspected in doping control, personal identification of the sample needs to be determined by short tandem repeat (STR) analysis using DNA. We established a method for extracting DNA from urine samples stored at −20 °C without using any additives or procedures, which is consistent with how samples are required to be managed for doping control. The method, using the Puregene® Blood Core kit followed by NucleoSpin® gDNA Clean‐up or NucleoSpin® gDNA Clean‐up XS kit, does not need any special instrument and can provide a purified extract with high‐quality DNA from up to 40 mL of urine suitable for STR analysis using an AmpF l STR® Identifiler® PCR amplification kit. Storing urine at −20 °C is detrimental to the stability of DNA. The DNA concentration of preserved urine could not be predicted by specific gravity or creatinine level at the time of urine collection. The DNA concentration of a purified extract (10 μL) was required to be >0.06 ng/μL to ensure a successful STR analysis. Thus, the required extraction volumes of urine preserved for 3–7 years at −20 °C were estimated to be 30 mL and 20 mL to succeed in at least 86% of men and 91% of women, respectively. Considering the long half‐life of DNA during long‐term preservation, our extraction method is applicable to urine samples stored even for 10 years, which is currently the storage duration allowed (increased from 8 years) before re‐examination in doping control. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : To cope with a case that the tampering of a urine sample is suspected in doping control, we established a urinary DNA extraction method suitable for the personal identification by STR analysis. The success ratio of STR analysis using 30 mL of urine samples from men cryopreserved for 3–7 years was at least 86%.